2013
DOI: 10.1186/gb-2013-14-11-r133
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and proteome quantification of a tumor model provides novel insights into post‐transcriptional gene regulation

Abstract: BackgroundGenome‐wide transcriptome analyses have given systems‐level insights into gene regulatory networks. Due to the limited depth of quantitative proteomics, however, our understanding of post‐transcriptional gene regulation and its effects on protein‐complex stoichiometry are lagging behind.ResultsHere, we employ deep sequencing and the isobaric tag for relative and absolute quantification (iTRAQ) technology to determine transcript and protein expression changes of a Drosophila brain tumor model at near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 77 publications
9
41
0
Order By: Relevance
“…A recent study by Jüschke et al (2013) reported similar results in Drosophila spp. : about 82% of all Kyoto Encyclopedia of Genes and Genomes annotated transcripts were expressed in fly heads, while 18% were not expressed.…”
Section: Discussionsupporting
confidence: 73%
“…A recent study by Jüschke et al (2013) reported similar results in Drosophila spp. : about 82% of all Kyoto Encyclopedia of Genes and Genomes annotated transcripts were expressed in fly heads, while 18% were not expressed.…”
Section: Discussionsupporting
confidence: 73%
“…50,53 Reliable quantification of post-transcriptional regulation remains a significant computational challenge. Here, we developed a resampling-based regression method to reliably quantify differential post-transcriptional regulation associated with MSI status.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to studying steady state mRNA and protein abundance, there are increasing research activities on the alterations of mRNA and protein abundance due to changing conditions or genetic variations, and dynamic changes in response to perturbations . Comparative analyses of proteomic and transcriptomic alterations provide a great opportunity to (1) investigate whether changing transcript abundance mediates protein alterations; (2) identify genes and functional categories with discordant mRNA‐protein alterations, suggesting potential protein‐level regulations; (3) discover the underlying regulators responsible for the protein‐level regulations.…”
Section: Integrative Analysis Of Mrna and Protein Abundancementioning
confidence: 99%